A universal route to fabricate bacterial cellulose-based composite membranes for simultaneous removal of multiple pollutants. Issue 69 (6th August 2021) - Gu, Yue; Li, Huaimeng; Ye, Mengxiang; Zhang, Xi; Zhang, Haimin; Wang, Guozhong; Zhang, Yunxia
Abstract : A self-standing, robust bacterial cellulose (BC)-based multifunctional composite membrane embedded with desirable nano-adsorbents has been successfully fabricated via a facile versatile strategy. Abstract : A self-standing, robust bacterial cellulose (BC)-based multifunctional composite membrane embedded with desirable nano-adsorbents has been successfully fabricated via a facile versatile strategy. As expected, the developed BC-based composite membrane enables the simultaneous and efficient removal of multiple co-existing pollutants.